2011
DOI: 10.1038/hr.2011.76
|View full text |Cite
|
Sign up to set email alerts
|

Significance of measuring oxidative stress in lifestyle-related diseases from the viewpoint of correlation between d-ROMs and BAP in Japanese subjects

Abstract: In recent years, oxidative stress has been postulated to be an important factor in the pathogenesis and development of lifestyle-related diseases. In this study, we investigated the association between the derivatives of reactive oxygen metabolites (d-ROMs), as an index of products of reactive oxygen species (ROS), and biological antioxidant potential (BAP), as an index of antioxidant potential. We also investigated the associations between d-ROMs or BAP and the risk factors for lifestyle-related diseases or m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
86
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(100 citation statements)
references
References 25 publications
8
86
2
Order By: Relevance
“…In fact, ROM has been widely-adopted as a biomarker for oxidative stress in both non-ruminants (Fukui et al, 2011, Jansen et al, 2013 and ruminants (Bernabucci et al, 2002, 2005, Trevisi et al, 2009, Celi et al, 2010. Although ROM concentrations in the present study were not affected by MET or CHOL supplementation, the substantially higher ROM starting at 4 d postpartum was indicative of an increased risk for the onset of oxidative stress.…”
Section: Biomarkers Of Oxidative Stresscontrasting
confidence: 47%
See 1 more Smart Citation
“…In fact, ROM has been widely-adopted as a biomarker for oxidative stress in both non-ruminants (Fukui et al, 2011, Jansen et al, 2013 and ruminants (Bernabucci et al, 2002, 2005, Trevisi et al, 2009, Celi et al, 2010. Although ROM concentrations in the present study were not affected by MET or CHOL supplementation, the substantially higher ROM starting at 4 d postpartum was indicative of an increased risk for the onset of oxidative stress.…”
Section: Biomarkers Of Oxidative Stresscontrasting
confidence: 47%
“…The increase in pro-oxidant levels is usually associated with increased risk of oxidative stress and therefore may be used as biomarkers. Because ROS concentration is an indicator of free radical production (Miller et al, 1993, Sugino, 2006, and when in excess can compromise cell function through damaging cellular lipid, protein, and DNA, it has been widely adopted as a biomarker for oxidative stress in non-ruminants (Fukui et al, 2011, Leufkens et al, 2012, Jansen et al, 2013 and ruminants (Bernabucci et al, 2002, 2005, Celi et al, 2010). In fact, the level of ROS is now considered as the gold standard for assessing total oxidative status (Celi, 2010).…”
Section: Pro-oxidants As Biomarkers Of Oxidative Stressmentioning
confidence: 99%
“…It has been suggested that enhanced oxidative stress may be closely related to the pathogenesis and development of arteriosclerosis [1][2][3][4] ; therefore, biomarkers of oxidative stress, including thiobarbituric acid-reactive substances 5) , oxidized low-density lipoprotein 6) , and reactive oxygen species (ROS), measured as derivatives of reactive oxygen metabolites (d-ROMs) 7) , are generally measured in patients with atherosclerosisrelated diseases; however, these assay methods require blood sampling.…”
Section: Introductionmentioning
confidence: 99%
“…The d-ROMs level is expressed in an arbitrary unit called the Carratelli unit (U.CARR) 9) . The d-ROMs test is not a fully established standard method of measuring oxidative stress; however, it has been recognized as an emerging plasma biomarker for the prediction of cardiovascular disease [10][11][12][13] . We measured the percent flow-mediated dilatation (%FMD) as a marker of endothelial dysfunction.…”
Section: Introductionmentioning
confidence: 99%